2020
DOI: 10.1186/s12886-020-01417-w
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of Glaucoma associated with Axenfeld-Rieger syndrome

Abstract: Background The surgical management of glaucoma associated with Axenfeld-Rieger Syndrome (ARS) is poorly described in the literature. The goal of this study is to compare the effectiveness of various glaucoma surgeries on intraocular pressure (IOP) management in ARS. Methods Retrospective cohort study at a university hospital-based practice of patients diagnosed with ARS between 1973 and 2018. Exclusion criterion was follow-up less than 1 year. The number of eyes with glaucoma (IOP ≥ 21 mmHg with corneal edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 35 publications
2
46
0
4
Order By: Relevance
“…However, many of the other forms of glaucoma represented in this study such as Axenfeld-Rieger syndrome, Peters Anomaly, microphthalmia, and aniridia are well-known to be refractory to both medications and angle surgery. Only a handful of studies have been able to access outcomes in these especially rare diseases [26,27]. More common forms of pediatric glaucomas such as primary congenital glaucoma and glaucoma following cataract surgery are often amenable to angle surgery and only the more complicated and difficult cases progress to trabecular bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the other forms of glaucoma represented in this study such as Axenfeld-Rieger syndrome, Peters Anomaly, microphthalmia, and aniridia are well-known to be refractory to both medications and angle surgery. Only a handful of studies have been able to access outcomes in these especially rare diseases [26,27]. More common forms of pediatric glaucomas such as primary congenital glaucoma and glaucoma following cataract surgery are often amenable to angle surgery and only the more complicated and difficult cases progress to trabecular bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most prominent are the ocular abnormalities that combine Axenfeld anomaly (posterior embryotoxon) and Rieger anomaly (iris hypoplasia), resulting in corectopia (irregular pupil), and pseudopolycoria (multiple pupils) ( Figure 4A ). Over 50% of affected individuals have glaucoma, which due to iris and trabecular meshwork abnormalities, often requires multiple surgeries to preserve vision ( Zepeda et al, 2020 ). In addition, individuals with ARS may have a distinctive craniofacial structure that includes telecanthus, maxillary hypoplasia, and broad flat nasal bridge, teeth abnormalities, such as oligodontia and microdontia, and congenital heart abnormalities.…”
Section: Ocular Neural Crest Derivatives: Lessons From Rare Ocular DImentioning
confidence: 99%
“…31,32 Lifelong monitoring is required as 50% of patients with ARA and up to 70% of patients with ARS have been reported to develop glaucoma. 33 The association of Axenfeld Rieger anomaly with systemic abnormalities is termed Axenfeld-Rieger syndrome. 30 Clinically it encompasses systemic midline abnormalities (dental anomalies, flattened nasal bridge and midface, and redundant peri-umbilical skin) in addition to the ocular findings.…”
Section: Aramentioning
confidence: 99%
“…A recent series of 32 patients with ARS found that trabeculectomy with anti-fibrotics and Baerveldt GDD showed the greatest success in obtaining IOP control. 33…”
Section: Aramentioning
confidence: 99%